The Proctolin Gene and Biological Effects of Proctolin in the Blood-Feeding Bug, Rhodnius prolixus - Orchard, Ian; Lee, Do Hee; Da Silva, Rosa; Lange, Angela B. (Frontiers in Endocrinology, 2011)
We have reinvestigated the possible presence or absence of the pentapeptide proctolin in Rhodnius prolixus and report here the cloning of the proctolin cDNA. The transcript is highly expressed in the central nervous system (CNS) with some low expression associated with peripheral tissues. The proctolin prepropeptide encodes a single copy of proctolin along with a proctolin-precursor-associated peptide. We have biochemically identified proctolin in CNS extracts and shown its distribution using proctolin-like immunoreactivity. Immunostained processes are found on the salivary glands, female and male reproductive organs, and heart and associated alary muscles. Proctolin-like immunoreactive bipolar neurons are found on the lateral margins of the common oviduct and bursa. Proctolin is biologically active on R. prolixus tissues, stimulating increases in contraction of anterior midgut and hindgut muscles, and increasing heartbeat frequency. Contrary to the previous suggestion that proctolin is absent from R. prolixus, proctolin is indeed present and biologically active in this medically-important bug.